Celebrity Endorsers and Purchase Decisions for Generation Z: Brand Image of Loreal Products (JEM17: Jurnal Ekonomi Manajemen, 2023)
The high demand for using beauty products and lots of competition make companies have to innovate in marketing strategies. The existence of the phenomenon in this study can be useful as material for consideration for marketing managers and entrepreneurs in marketing products. So consumers can understand more trending products and fulfill consumer desires in their buying behavior. This study aims to determine celebrity endorser's purchasing decisions for Generation Z which is mediated by brand image on L'Oreal products. The number of samples in this study were 100 respondents who had bought L'Oreal products. The data collection technique used a purposive sampling method with a questionnaire conducted on Z generation women at the Golden Kediri Supermarket. Data analysis of the results of this study: celebrity endorser has a positive and significant effect on brand image, and brand image has a positive and significant effect on purchasing decisions, then celebrity endorser has no direct significant effect on purchasing decisions. Testing the intervening variables shows that there is an indirect effect on purchasing decisions through the brand image variable. Keywords: Celebrity Endorser, Brand Image, Generation Z, Purchase Decision.